Kebijakan Pemenuhan Kebutuhan dasar lansia dan Optimum Aging: kajian Literatur - Widinarsih, Dini; Departemen Ilmu Kesejahteraan Sosial, Universitas Indonesia, (UI Scholars Hub, 2022)
Elderly (elderly) is someone who has reached the age of 60 years and over. The United Nations Department of Economic and Social Affairs (UNDESA, 2015) projects that the number of people aged 60 years and over will reach 2 billion by 2050, and will continue to increase to more than three times by 2100. The increasing number of elderly population makes the elderly one of the It is important to pay attention to groups so that they do not become an economic and social burden. Therefore, it is necessary to utilize the potential of the elderly and seek forms of fulfilling the rights of the elderly to achieve optimal quality of life (optimum aging). This article aims to describe the policy of meeting the basic needs of the elderly in order to become optimum aging. This article was compiled using the literature review method on official reports, statistics and previous research. The literature review conducted includes context review, methodological review, and theoretical review. From the context review, it was revealed that there were 8 (eight) basic needs of the elderly including health services, food, housing, finance, security, education, self-actualization and social relations. It was also revealed that there are several policies in several countries to address the problems of the elderly. The core results of the methodological review show that the type of qualitative approach and literature review is widely used in research related to the elderly. From the theoretical review, it can be seen that the use of hierarchical theory of basic human needs for the elderly helps in understanding the problems faced by the elderly and the appropriate policies to deal with them